Design and Development of Anti-fungal Topical Gel Loaded with Solid Lipid Nanoparticles for Wound Healing - Girish Meravanige1; Ranjitha B2 Prakash Goudanavar2 GSN Koteswara Rao3 B Nirmala Devi4 N. Raghavendra Naveen2, Afzal Haq Asif5 Sree Harsha Nagaraja6,7 Mohammed Monirul Islam8 Pavan Kumar Pavagada Sreenivasalu9, Mallikarjun Telsang10 , Krishna Swaroop Duddi Sreehari1
The topical administration of anti-fungal drugs by Solid Lipid Nanoparticles (SLNs) has enormous potential. This study aimed to develop a topical 5-flucytosine-loaded SLNs gel to improve the efficacy of the well-known anti-fungal drug in the treatment of wound healing. Materials and Methods: In order to create 5-flucytosine SLNs, a five-level, two-factor Central-composite design was used. Stearic acid and Poloxamer 407 concentrations of surfactants were chosen as independent factors, and particle size and %Entrapment Efficiency (%EE) were chosen as dependent variables. The produced 5-Flucytosine-SLNs were examined using SEM analysis, zeta potential, polydispersity index, and particle size measurements. Additionally, Carbopol 934 was used to incorporate the improved 5-Flucytosine-SLN formula into gel. Results: The outcomes demonstrated that 5-Flucytosine-SLNs had colloidal sizes with an essentially spherical shape and no aggregation. 5-Flucytosine-SLNs were discovered to have a particle size of 720.4 nm and an Entrapment Efficiency (EE) of 90.28%. The in vitro release, among other assessment criteria, was evaluated for the improved SLN gels. Conclusion: The study's conclusions imply that the topical gels made with 5-Flucytosine-loaded SLNs must be effective in the management of wound healing.